Is ethanol production responsible for the increase in corn prices?. (November 2022) - Kocak, Emrah; Bilgili, Faik; Bulut, Umit; Kuskaya, Sevda
Abstract: This paper aims to investigate the effects of the production of ethanol, a renewable biofuel, oil prices, population, and exchange rate on corn prices in the US (1985:m1-2020:m7) using a nonlinear smooth transition model. According to the findings, (i) ethanol production (β1  = 0.072, p < 0.01) has an increasing effect on corn prices. (ii) Oil prices (β2  = 0.064, p < 0.05) and population (β3  = 0.851, p < 0.01) put a pressure on corn prices. (iii) The increase in the real exchange rate (β4  = −2.142, p < 0.01) has a decreasing effect on corn prices. The estimation results provide several critical policy implications for ethanol-food competition within the framework of sustainable development policies. First, ethanol production puts pressure on corn prices. Second, policy-oriented research on the biofuel-food competition can provide guidance to ensure sustainability. Finally, in the transformation process of the ethanol industry, technological innovations (use of second or third-generation biofuels) can moderate the food-fuel nexus.